GAMBARAN SANITASI SARANA PRODUKSI DAN PERSONAL HIGIENE KARYAWAN DI INDUSTRI RUMAH TANGGA PANGAN MI LETHEK “X” DUSUN BENDO TRIMURTI SRANDAKAN BANTUL TAHUN 2022 - anis safety; Agus Kharmayana Rubaya; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2022)
The Sanitation Food Home Industry Production facilities are objects of an application to maintain the safety of food products. The food poisoning cases reported by BPOM in 2019 on average occurred because household food processing did not implement good food production methods. The purpose of this study was to determine the sanitary picture of production facilities and personal hygiene of employees at IRTP Mi Lethek "X". This type of research is a survey using descriptive analysis and the method used is observation. The descriptive analysis in this study aims to describe the sanitation of production facilities, personal hygiene, and the potential for contamination of cattle at IRTP Mi Lethek "X" Bendo, Trimurti, Srandakan, Bantul by focusing on the potential danger of cattle as a source of contaminants. This research instrument uses BPOM Perka Number HK.03.1.23.04.12.2206 of 2012 concerning Good Food Production Methods for the Home Industry. Based on descriptive analysis, the sanitation of home industry production facilities in Lethek Noodle "X" has a serious category of 7 deviations. These serious deviations have the potential to affect lethek noodles. The critical category of 4 deviations will affect the safety of the lethek noodle and for the major category, there is 1 deviation that has the potential to affect the efficiency of safety control of the lethek noodle. The results of personal hygiene research of employees who do not meet the requirements are 68.40% and the potential for contamination of cattle is 66.70%. This can potentially affect the safety of lethek noodles.